Akomodasi Komunikasi Komunitas Hindu Bali Sebagai Penduduk Pendatang Di Daerah Transmigrasi - Astraguna, I Wayan (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2025)
This research aims to examine the communication strategies used by the Balinese Hindu community in adapting as a migrant group in the transmigration area of ​​South Sulawesi. Using a descriptive qualitative approach and Howard Giles' Communication Accommodation theory, this research found that the Balinese Hindu community implemented convergence and divergence strategies in maintaining social harmony. The active participation of women and vulnerable groups also shows inclusiveness in the adaptation process. This research confirms that communication is a key factor in successful social integration and preventing conflicts with SARA nuances (Ethnicity, Religion, Race) that can arise due to economic inequality. Thus, the findings of this research lie in emphasizing that the success of social integration is not only determined by economic aspects or state policy, but is deeply influenced by cross-cultural communication skills carried out consciously, strategically and participatively by the community itself.